Multimodal Therapeutic Management in a Intact Male Cat with Cystitis, Crystalluria and Urethral Obstruction - Egrina Sonta Bako; I Nyoman Suartha; I Putu Gede Yudhi Arjentinia; Gede Sastra Darma Yasa (Universitas Airlangga, 2026)
Background: Feline Lower Urinary Tract Disease is a complex clinical condition in cats that commonly results in inflammation of the urinary bladder, crystalluria, bacterial infection, and urethral obstruction, particularly in male cats. Purpose: This case report aims to describe the clinical course, diagnostic findings, and effectiveness of multimodal therapeutic management in a male cat with bacterial cystitis accompanied by persistent struvite crystalluria and partial urethral obstruction. Case(s): Ragdoll (male, 2 years old) presenting with stranguria, pollakiuria, hematuria, and lethargy underwent comprehensive clinical evaluation supported by hematological analysis, urinalysis, and ultrasonography. Case Management: Management involved a multimodal therapeutic approach including intravenous fluid therapy, urethral catheterization, antibiotics, anti-inflammatory agents, urethral relaxants, glycosaminoglycan supplementation, a therapeutic urinary diet, and environmental modification. Urethral obstruction was managed with smooth catheter, secured for four days, periodically flushed with sterile saline to reduce debris and crystals. Serial evaluations were conducted up to day 60. Physical examination revealed mild dehydration, pale mucous membranes, and a distended urinary bladder. Hematological examination demonstrated leukocytosis, lymphocytosis, granulocytopenia, and thrombocytopenia consistent with systemic inflammation. Initial urinalysis showed hematuria, marked proteinuria, positive leukocytes and nitrites, a urine specific gravity of 1.015, and moderate to abundant struvite crystals. Ultrasonographic findings included thickening of the urinary bladder wall with hyperechoic sediment and increased cortical echogenicity of the left kidney. Multimodal therapy resulted in progressive clinical and laboratory improvement. Evaluation on day 60 showed normalization of hematological parameters, near-normal urinalysis results, and resolution of urinary bladder sediment. Conclusion: Clinical insights gained from this case emphasize that dietary compliance, stress reduction, and vigilant long-term surveillance are critical for resolving complex FLUTD.